HUBUNGAN CARA BELAJAR DAN KONDISI EKSTERNAL BELAJAR DENGAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS - Nur Hasanatul Azizah; Mardono Mardono; Agung Haryono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2015)
Correlational descriptive study aimed to elaborate on the relationship between the variables in the study. The variable in this study is a way of learning (X1), the external conditions of learning (X2), and the learning outcomes (Y). Subjects numbered 72 students MA AL-AZIZ Dampit District of Malang. The survey results revealed that there is a relationship between learning with learning outcomes on economic subjects, and there is a relationship between the external conditions of learning with learning outcomes on economic subjects.